2022
DOI: 10.3389/fonc.2022.916661
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipid Metabolism in Gastric Cancer

Abstract: Gastric cancer has been one of the most common cancers worldwide with extensive metastasis and high mortality. Chemotherapy has been found as a main treatment for metastatic gastric cancer, whereas drug resistance limits the effectiveness of chemotherapy and leads to treatment failure. Chemotherapy resistance in gastric cancer has a complex and multifactorial mechanism, among which lipid metabolism plays a vital role. Increased synthesis of new lipids or uptake of exogenous lipids can facilitate the rapid grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 228 publications
0
20
0
Order By: Relevance
“…We speculated that ABCA1 may be involved in the invasion and metastasis of gastric cancer through the PI3K-Akt signaling pathway. Moreover, previous studies showed PI3K/Akt/mTOR signaling pathway as an important signaling pathway in lipid metabolism in gastric cancer ( 57 , 79 ). In addition, our study revealed that ABCA1 expression in STAD was closely associated with immune infiltration, MSI, TMB, and neoantigen loads.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We speculated that ABCA1 may be involved in the invasion and metastasis of gastric cancer through the PI3K-Akt signaling pathway. Moreover, previous studies showed PI3K/Akt/mTOR signaling pathway as an important signaling pathway in lipid metabolism in gastric cancer ( 57 , 79 ). In addition, our study revealed that ABCA1 expression in STAD was closely associated with immune infiltration, MSI, TMB, and neoantigen loads.…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, the increased level of mitochondrial fatty acid β-oxidation not only provides sufficient energy for the growth and metastasis of cancer cells, but also participates in the transduction of lipid rafts and lipid modified signaling molecules, which further promotes tumor progression. In addition, drug resistance in gastric cancer may also be related to lipid metabolism ( 57 , 58 ). However, no article has yet reported on the construction of risk models for genes related to lipid droplet metabolism in gastric cancer to predict survival prognosis and immunotherapy efficacy in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting Akt/b-catenin and Ras/MEK/ERK signaling pathways, phosphatidylcholine metabolism also contributes to addressing medication resistance [ 33 ]. Notably, lipid reprogramming changes intercellular lipid metabolism and immune cells' pharmaceutical resistance in the tumor microenvironment [ 2 ]. In present study, we interestingly discovered that GC patients with unfavorable plasma lipid metabolism profiles allowed by the 1 H-NMR platform had a significantly shorter OS under postoperative chemotherapy, further supporting the hypothesis that lipid metabolism may play an important role in antitumor drug resistance in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism dysregulation is a significant alteration in the development of cancer, involving proliferation, invasion, metastasis, and therapeutics in cancer due to cancer cells harnessing lipid metabolism to get the elements needed to make biological membranes, energy, as well as signaling molecules [1]. Current researches suggest that lipid metabolism changes in cancer are capable of mediating antitumor drug resistance by up-regulating lipogenesis and lipolytic enzyme expression [2]. In a mouse model, tumor tissues were reported to be able to increase the expression of proteins involved in lipid metabolism in gastric cancer (GC) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells dysregulate metabolic pathways by high rates of lipid synthesis to support rapid growth 29,30 . GC cells have been found to accelerate lipid synthesis and reduce lipid hydrolysis 31,32 , which leads to increased accumulation of excessive lipids in lipid droplets (LDs) 31,32 . More importantly, dysregulated lipid metabolism has been shown to promote cancer metastasis 33 , including PM 34 .…”
Section: Introductionmentioning
confidence: 99%